An empirical assessment of drug trafficking trends from Latin America into the United States: the role of fishing vessels - Chiang, Ho-Tu (Deviant behavior, 2025)
Drug trafficking is one of the most serious crimes of our century. The market reach is estimated to be over $500 billion annually, with a particularly robust user base found in the Americas and Europe. The United States, in particular, is one of the strongest consumer markets for drugs originating from Latin America. While such serious drugs as cocaine have been trafficked into the United States using various means, one method that has been gaining attention is the use of fishing vessels. Nevertheless, studies on the role of fishing vessels in trafficking drugs from Latin America into the United States are rare. To fill this gap, this research uses fishing vessel interception data obtained through Freedom of Information Act request from the United States Coast Guard for the years 2015-2021. Informed by crime science theory, this research examines the geospatial and temporal trends associated with drug trafficking by fishing vessels, as well as such vessel characteristics as flags they carried at the time of interception, and vessel type. Policy implications are discussed in light of the main research findings.